Somatostatin receptor biology in neuroendocrine and pituitary tumours: part 1--molecular pathways. - Cakir, M; Dworakowska, D; Grossman, A (2010)
Neuroendocrine tumours (NETs) may occur at many sites in the body although the majority occur within the gastroenteropancreatic axis. Non-gastroenteropancreatic NETs encompass phaeochromocytomas and paragangliomas, medullary thyroid carcinoma, anterior pituitary tumour, broncho-pulmonary NETs and parathyroid tumours. Like most endocrine tumours, NETs also express somatostatin (SST) receptors (subtypes 1-5) whose ligand SST is known to inhibit endocrine and exocrine secretions and have anti-tumour effects. In the light of this knowledge, the idea of using SST analogues in the treatment of NETs has become increasingly popular and new studies have centred upon the development of new SST analogues. We attempt to review SST receptor (SSTR) biology primarily in neuroendocrine tissues, focusing on pituitary tumours. A full data search was performed through PubMed over the years 2000-2009 with keywords 'somatostatin, molecular biology, somatostatin receptors, somatostatin signalling, NET, pituitary' and all relevant publications have been included, together with selected publications prior to that date. SSTR signalling in non-neuroendocrine solid tumours is beyond the scope of this review. SST is a potent anti-proliferative and anti-secretory agent for some NETs. The successful therapeutic use of SST analogues in the treatment of these tumours depends on a thorough understanding of the diverse effects of SSTR subtypes in different tissues and cell types. Further studies will focus on critical points of SSTR biology such as homo- and heterodimerization of SSTRs and the differences between post-receptor signalling pathways of SSTR subtypes.